Negative regulation of the bovine papillomavirus E5, E6, and E7 oncogenes by the viral E1 and E2 genes. - Vande Pol, S B (1995)
Papillomaviruses induce benign squamous epithelial lesions that infrequently are associated with uncontrolled growth or malignant conversion. The virus-encoded oncogenes are clearly under negative regulation since papillomaviruses can latently infect cells and since different levels of viral oncogene expression are seen within the layers of differentiating infected epitheliomas. We used bovine papillomavirus type 1 (BPV-1) to investigate the mechanisms involved in the negative regulation of transformation. We found that the following two distinct and interacting mechanisms negatively regulate BPV-1 transformation effected by virally encoded trans-acting factors: (i) E2 repressors suppress transformation by the E6 and E7 oncogenes, and (ii) E1 and the E2 transactivator suppress transformation by the E6, E7, and E5 oncogenes. These systems interact in that the E2 repressors function to relieve the transformation suppression effected by the E1 and E2 transactivator genes. A BPV-1 mutant that lacked E2 repressors and E1 had greatly augmented transformation capacity. Analysis of this mutant revealed that the enhanced transformation was due to expression of the E6 and E7 genes in the absence of E5, revealing a previously unappreciated potency and synergy for the BPV-1 E6 and E7 oncogenes.